Review of the Healing Potential of Burn Wounds with Aloe Vera Extract Cream: The Influence of Formula and Virgin Coconut Oil Application: Review of the Healing Potential of Burn Wounds with Aloe Vera Extract Cream: The Influence of Formula and Virgin Coconut Oil Application - Sidiq, Fahmi (Corespub, 2023)
This paper discusses the potential of using Aloe vera extract cream with various formulas, including the incorporation of Virgin Coconut Oil (VCO) as a cream base, for burn wound healing. The study aims to investigate the healing effects of second-degree burn wounds in mice using Aloe vera extract cream with different formulas. Phytochemical analysis identified the presence of phenols, tannins, and saponins in the Aloe vera extract. The results of the wound healing tests indicate that Aloe vera extract creams with different formulas have the potential to accelerate healing, with a healing time range of 8 to 14 days. Formulas containing VCO as a cream base showed faster healing, likely due to the medium-chain saturated fatty acid content in VCO that supports tissue regeneration. Aloe vera extract also possesses cleansing and antiseptic properties that can prevent infections in wounds. Although healing times varied among the different formulas, the main conclusion is that Aloe vera extract creams have the potential to support the healing of second-degree burn wounds.